The Location and Diameter of the Primary Maxillary Sinus Ostium in Malaysians: A Cone-Beam Computerized Tomography Study - Sanual S. Peter; Phrabhakaran Nambiar; Subramaniam Krishnan; Nisreen Mohammed AL-Namnam (Journal of Big Data Research, 2020)
Rhinosinusitis is one of widely spread diseases in the region and the role of the anatomical variations in its pathogenesis remains unresolved. A retrospective study using CBCT scan was employed to locate and measure the diameter of 320 primary maxillary ostium (PMO) (n = 160 subjects) among the Malay and Chinese populations (Mongoloid race) in Malaysia. Image analysis was performed using the i-CAT Vision Software, employing the multiplanar reconstruction window in which axial, coronal and sagittal planes were visualized in 0.3 mm intervals. The mean diameter of the PMO was significantly larger in the Chinese than the Malay. Females had larger size than the male and bilateral asymmetry was noticed, where the right side PMO was larger than the left side (p < 0.05). In addition, PMO opened more in the posterior third position of the hiatus semilunaris (61.9%) than anterior and middle third. The PMO showed a statistically significant posteriorly placed position in the Chinese than the Malays and this was more evident in the right side PMO (p < 0.01). In conclusion, the PMO commonly opens in the posterior third of the hiatus semilunaris and its diameter is significantly greater in the Chinese female with evidence of bilateral asymmetry. Awareness the anatomical variation of the Ostium diameter and location among the Malay and Chinese populations potentially has important clinical effects during surgical procedures.
Keywords: Primary maxillary sinus ostium